2014
DOI: 10.1159/000357554
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Fat Supplementation Improves Protein Absorption in Premature Infants with an Enterostomy

Abstract: Background: Early enteral fat supplementation and fish oil (FO) stimulates post-resection intestinal adaptation in rats and increases fat absorption in premature infants with bowel resection and an enterostomy. Objective: To test the hypothesis that early fat supplement and FO increases post-resection protein absorption, intestinal RNA, protein without decreasing intestinal arachidonic acid (AA) in premature infants with an enterostomy. Methods: 36 premature infants (<2 months old) with an enterostomy after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…In line with these experimental findings a highfat diet, including fish oil stimulated protein and fat absorption as well as intestinal RNA and protein content in preterm neonates with an enterostomy [50][51][52]. Between the treatment and the control group there was no difference in weight gain, ostomy output, and duration of parenteral nutrition but the treatment group had lower bilirubin, fewer sepsis evaluations, less exposure to antibiotics, and had greater weight and length gain after reanastomosis [50].…”
Section: Dietary Fatsupporting
confidence: 55%
“…In line with these experimental findings a highfat diet, including fish oil stimulated protein and fat absorption as well as intestinal RNA and protein content in preterm neonates with an enterostomy [50][51][52]. Between the treatment and the control group there was no difference in weight gain, ostomy output, and duration of parenteral nutrition but the treatment group had lower bilirubin, fewer sepsis evaluations, less exposure to antibiotics, and had greater weight and length gain after reanastomosis [50].…”
Section: Dietary Fatsupporting
confidence: 55%
“…Clinical nutrition intervention was widely used to compensate for preterm infants, especially babies with very low birth weight [7,8], such as breast milk forti er, high energy total nutrition formula. Although some of the low-quality evidence available have shown that speci c nutrients in uence the physical growth and mental development of premature infants, the results are contradictory due to study of object and design.…”
Section: Introductionmentioning
confidence: 99%